Measuring Spatial Expansion of Tehran Metropolis and its Impact on Environmental Changes - Asghar Teymouri; Jamileh Tavakolinia; Abolfazl Meshkini (تحقیقات کاربردی علوم جغرافیایی)
Increasing urbanization in the urbanized world has posed major challenges to the sustainability of metropolitan areas, especially in developing countries in various aspects of sustainable development, and has provided them with the prospect of unsustainable development. Excessive land use and its consequent land use changes and land cover are one of the environmental problems caused by the high concentration of population and activity in metropolitan areas. This study is an applied one in order to monitor the environmental changes caused by spatial expansion of Tehran metropolitan area by descriptive-analytical method and by using remote sensing and GIS techniques land use changes and land cover caused by spatial expansion of Tehran metropolis. Has evaluated and analyzed Tehran. The results indicate that the area of ​​land increased from 34316.1 hectares in 1365 to 68252 67.95 in 1595/6117 hectares related to changes in agricultural lands, orchards and water area. Be it. The results of the Markov Chain Model prediction of the probability of land use changes and land cover up to 1405 also indicate that land use and land cover changes will continue in favor of constructed lands. It is concluded that Tehran's metropolitan area has expanded beyond the demographic and ecological thresholds and has led to a significant structural disruption to the environment by moving toward the natural environment. Accordingly, the need to pay attention to new approaches to urban development as well as to provide decentralization scenarios can be a major step towards resolving environmental problems caused by over-spatial expansion.